Protein O-mannosylation in the early secretory pathway - Neubert, Patrick; Strahl, Sabine (Current opinion in cell biology, 2016)
Protein O-mannosylation and N-glycosylation are essential post-translational modifications, which initiate in the endoplasmic reticulum (ER). In yeast, the two glycosylation machineries act at the Sec61 translocon complex where they can even compete for certain substrate proteins. N-linked glycans play a crucial role in the ER quality control of glycoproteins. In recent years, it became clear that in addition to its important functions for cell surface proteins, O-mannosylation impacts the ER protein homeostasis. These glycans can exclude unfavorable folding intermediates from futile folding attempts, increase the solubility of irreversibly misfolded proteins, and even mark them for degradation. O-Mannose glycoproteomics now captures the molecular complexity of this modification opening exciting opportunities to explore further roles of O-mannosylation in the early secretory pathway.